Agreement between SARS-CoV-2 Antibody Test Results Using FIA and ECLIA Methods in Post-COVID-19 Infection and Sinovac Vaccination - Hubertus, Johanis; Sidharta, Brigitte Rina Aninda; Kurniati, Amiroh (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Coronavirus Disease 2019 (COVID-19) is a pandemic that needs to be urgently addressed through the formation of antibodies, such as vaccination. Automated SARS-CoV-2 antibody tests in hospitals are limited due to maintenance issues and high costs. This study aimed to determine the agreement of SARS-CoV-2 antibody test results using the FIA and ECLIA methods in post-COVID-19 infection and Sinovac vaccination. An observational analytical study with a cross-sectional approach was conducted at Dr. Moewardi Hospital from September to November 2022. The FIA method (FRENDTM NanoEntek) and ECLIA method (Cobas e411) were employed, revealing significant differences and strong correlations in both the COVID-19 infection group (r=0.9999, p<0.0001) and the Sinovac vaccination group (r=0.997, p<0.0001). The Passing and Bablok test showed systematic, proportional, and random differences in both the COVID-19 infection group (95% CI = -65.60 to -41.97; 95% CI = 3.42 to 3.70; 95% CI = -4.76 to 4.76) and the Sinovac vaccination group (95% CI = -21.71 to -8.69; 95% CI = 2.23 to 2.96; 95% CI = -12.37 to 12.37). In conclusion, there is no method of agreement between the results of SARS-CoV-2 antibody testing using the FIA and ECLIA methods in both post-COVID-19 infection and post-Sinovac vaccination groups